The cultural environment surrounding the text, "the reasons for revelation," and its impact on guiding the Qur’anic meaning. - Messaoud, GADI (Journal of Ecohumanism, 2026)
This study aims to elucidate the impact of the cultural environment surrounding the occasions of revelation on the interpretation of the Quranic text, by highlighting the close relationship between the Quranic discourse and the social and cultural context in which it was revealed. The Holy Quran addressed a society with its own customs, traditions, and issues, making understanding this environment crucial for comprehending the text’s intent and grasping its true meaning. The occasions of revelation, with their inherent cultural and social context, contributed to clarifying Quranic objectives, correcting interpretations, and preventing uncontrolled misinterpretations. The study also revealed that considering the specificity of the cultural context does not limit the text’s meaning to the time of revelation, but rather provides an entry point for understanding the relationship between the specific and the general, and between historical circumstances and the enduring relevance of Quranic guidance across time.